Economic Growth and Integration in Central America - Schipke, Alfred (Occasional Papers; Occasional Paper ;, 2007)
How to entrench hard-won gains, increase resilience to shocks, and improve growth performance to reduce poverty? As Central America moves forward in regaining macroeconomic stability, these are the challenges. This study analyzes Central America's real, fiscal, monetary, and financial sector policies at the regional level, starting with a review of growth performance and the macroeconomic implications of remittances. It then looks at the sustainability of pension systems, financial system development, sovereign debt vulnerabilities, and ways to sustain progress in reducing inflation by strengthening the credibility of central banks.